Myocardial injury before noncardiac surgery - Chen, Zhibing; Zhang, Yitao; Zeng, Weijie; Ye, Lin; Yu, Changda; Shi, Fan (Frontiers in Cardiovascular Medicine, 2023)
Non-cardiac surgical procedures present a significant circulatory stress and can potentially trigger cardiovascular events, such as myocardial infarction and heart failure. Myocardial injury before non-cardiac surgery is associated with an increased risk of mortality and major cardiovascular complications during perioperative period, as well as up to 5 years after non-cardiac surgery. While the definition of preoperative myocardial injury is not yet clear, it is generally understood as myocardial injury resulting from various causes of troponin elevation without acute coronary syndrome prior to surgery. Detecting preoperative myocardial injury through routine troponin monitoring is crucial for reducing perioperative risk, but it is also challenging. The aim of this review is to discuss the definition of preoperative myocardial injury, its pathophysiology, implications on clinical practice and decision-making for patients with elevated troponin levels before non-cardiac surgery.